2021
DOI: 10.1007/s00170-021-06845-6
|View full text |Cite
|
Sign up to set email alerts
|

Considering multiple process observables to determine material model parameters for FE-cutting simulations

Abstract: Analyzing the chip formation process by means of the finite element method (FEM) is an established procedure to understand the cutting process. For a realistic simulation, different input models are required, among which the material model is crucial. To determine the underlying material model parameters, inverse methods have found an increasing acceptance within the last decade. The calculated model parameters exhibit good validity within the domain of investigation, but suffer from their non-uniqueness. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…For modeling the plasticity of the workpiece, the Johnson-Cook constitutive model was utilized. The Johnson-Cook model is one of the most commonly used material model for cutting simulations [14]. Its mathematical expression is shown in Eq.…”
Section: Simulation Of Specific Cutting Forcesmentioning
confidence: 99%
“…For modeling the plasticity of the workpiece, the Johnson-Cook constitutive model was utilized. The Johnson-Cook model is one of the most commonly used material model for cutting simulations [14]. Its mathematical expression is shown in Eq.…”
Section: Simulation Of Specific Cutting Forcesmentioning
confidence: 99%
“…The authors claim the approach can inversely re-identify the parameters of the constitutive model in a few iterations when compared with his earlier work [23]. In [25], Hardt et al extended his work to include the automation of the post-processing of the results and increased the number of observables in the objective function. The authors concluded that different parameter sets identified by the algorithm result in the prediction of identical temperature, stress, and strain profiles, highlighting the non-uniqueness.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent progress of computer and software science, finite element technology has been extensively adopted in the cutting field, providing support for the study of chip formation, cutting temperature prediction, microstructure evolution, cutting force and residual stress. 2333 At present, finite element technology is generally regarded as an indispensable method for investigating the cutting mechanisms of titanium alloys. 3442 Hu et al 34 established a 2D finite element model to explore the effect of the ultrasonic method on the ultra-precision cutting of Ti6Al4V alloy under different cutting conditions.…”
Section: Introductionmentioning
confidence: 99%